Uji Aktivitas Antibakteri Ekstrak Etanol Daun Pegagan (Centella asiatica (L.) Urb ) pada BakteriStaphylococcus aureus - Angraini Siregar; Maya Sari Mutia; Ali Napiah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Pegagan leaves are one of the plants used as medicine with the latin name Centella asiatica (L.) Urb. The results of phyitochemical screening that have been carried out show that pegagan leaves contain tannin, steroid and flavonoid hich have an antibacterial function by inhibiting bacterial action in cell formation and even growth. The purpose of this study was to determine the activity of extract of pegagan leaf in inhibiting Staphylococcus aureus. This type of research is in experiment with 6 treatments, namely DMSO as a negative control, an chloramphenicol as positive control and pegagan leaf extract at concentrations 25%, 50%, 75% and 100%. Extraction process of pegagan leaf by maceration method and in the antibacterial test using disc diffusion. Based on the results of the study show that pegagan leaf has antibacterial effect against Staphylococcus aureus which at concetration 25% is 7.7 mm, 50% is 10.37 mm, 75% is 12.4 mm and 100% is 12.18 mm.